أثر الانفاق العام الاجتماعي على التنمية الاجتماعية في الجزائر (1990-2018) – دراسة قياسية باستخدام نموذج Var وسببية تودا يماموتو - - حفوظة الأمير, عبد القادر; بن أحمد, جيلالي (جامعة الوادي - University of Eloued, 2022)
This research aims to study the impact of the income redistribution policy on social development in Algeria by standing on the role that social public spending can play as the most important mechanism of income redistribution mechanisms in the areas of social development, especially education, health, housing and social transfers, as well as evaluating most of the indicators relevant to these areas. In this research, we conducted a standard study of the impact of social public spending on social development (Gini coefficient) using the autoregressive ray test (VAR) and Toda & Yamamoto causality test for the period (1990-2018), and we came to the conclusion that social public spending as a policy The redistribution of national income did not fulfill its distributive role with the expected efficiency and effectiveness, in order to achieve comprehensive and equitable social development in Algeria
The Impact of Social Public Expenditure on Social Development in Algeria 1990-2018 A Model Study VAR Model and Causality Toda-Yamamoto
مقال
Keywords: الانفاق العام الاجتماعي، إعادة توزيع الدخل، التنمية الاجتماعية، تودايماموتو، متجه الانحدار الذاتي.